Correction to: Menopausal Symptoms in Underserved and Homeless Women Living in Extreme Temperatures in the Southwest by Mukarram, et al. Womens Health Rep 2021;2(1):44?52; doi: 10.1089/whr.2020.0083 (Mary Ann Liebert, 2023)
In the 2021 volume of Women's Health Reports (vol. 2, no. 1; pp. 44?52), the article entitled ?Menopausal Symptoms in Underserved and Homeless Women Living in Extreme Temperatures in the Southwest? by Mukarram, et al. requires correction. The authors have discovered that an error was made in calculating the Greene Climacteric Scale scores. Scores were erroneously calculated using a scale of 1-4 instead of a scale of 0-3, which is the standard in the field. The scores have been recalculated, and the authors have confirmed that the relationships and statistically significant findings that were reported are not affected by the recalculation. The article has been revised as follows: In the ?Results? section of the abstract, the second sentence originally read: The total GCS score was a mean of 41???15.0; out of 63 indicating significant symptoms, the psychological and somatic clusters were highest. This has been updated to: The total GCS score was n?=?104: Mean (SD) 19.8 (15.3); out of 63 indicating significant symptoms, the psychological and somatic clusters were highest. In the section ?Menopausal symptoms during both winter and summer (GCS)? on page 47, the second sentence originally read: The total GCS score was a mean of 41???15.0, consistent with a medium level of symptom bother, with the highest scores in the psychological, somatic, depression, and anxiety clusters (Table 1). This has been updated to: The total GCS score was n?=?104: Mean (SD) 19.8 (15.3), consistent with a medium level of symptom bother, with the highest scores in the psychological, somatic, depression, and anxiety clusters (Table 1). The data in the last section of Table 1, ?Greene Climacteric Scale score, mean (SD)? has been revised. The table originally published as: Summer (N?=?54) Winter (N?=?50) p n (%) n (%) Greene Climacteric Scale score, mean (SD) ?Total 40 (15.2) 42.4 (15.3) 0.46 ?Psychological cluster 20.7 (8.5) 22.8 (8.8) 0.27 ?Anxiety subcluster 9.9 (4.3) 10.3 (4.5) 0.75 ?Depression subcluster 10.8 (4.6) 12.5 (5.0) 0.10 ?Somatic cluster 13.4 (6.1) 14.3 (6.2) 0.55 ?Vasomotor cluster 4.1 (1.9) 3.5 (2.0) 0.11 ?Sexual interest cluster 1.8 (1.0) 1.8 (1.1) 0.83 It has been revised to: Summer (N?=?54) Winter (N?=?50) p n (%) n (%) Greene Climacteric Scale score, mean (SD) ?Total 19.0 (15.2) 21.0 (15.6) 0.54 ?Psychological cluster 9.7 (8.5) 11.5 (9.1) 0.41 ?Anxiety subcluster 4.9 (4.3) 5.3 (4.5) 0.76 ?Depression subcluster 4.8 (4.6) 6.2 (5.1) 0.21 ?Somatic cluster 6.4 (6.1) 7.3 (6.2) 0.56 ?Vasomotor cluster 2.1 (1.9) 1.5 (2.0) 0.11 ?Sexual interest cluster 0.8 (1.0) 0.8 (1.1) 0.83 The data in the last section of Table 2, ?Vasomotor symptom cluster score by GCS? has been revised. The table originally published as: Not at all (N?=?45) A little (N?=?25) Quite a bit (N?=?15) Extremely (N?=?6) Total (N?=?91) p Vasomotor symptom cluster score by GCS ?N 38 18 14 6 76 <0.001b ?Mean (SD) 2.2 (0.54) 4.2 (0.88) 5.9 (0.77) 8.0 (0.00) 3.8 (1.98) ?Median 2.0 4.0 6.0 8.0 3.0 ?Range 2.0, 4.0 3.0, 6.0 4.0, 7.0 8.0, 8.0 2.0, 8.0 It has been revised to: Not at all (N?=?45) A little (N?=?25) Quite a bit (N?=?15) Extremely (N?=?6) Total (N?=?91) p Vasomotor symptom cluster score by GCS ?N 38 18 14 6 76 <0.001b ?Mean (SD) 0.2 (0.54) 2.2 (0.88) 3.9 (0.77) 6.0 (0.0) 1.8 (1.98) ?Median 0.0 2.0 4.0 6.0 1.0 ?Range 0.0, 2.0 1.0, 4.0 2.0, 5.0 6.0, 6.0 0.0, 6.0 In the section ?Subanalysis? on page 48, the second and third sentences originally read: On the GCS, uninsured women reported fewer symptoms overall compared to insured women (37???13.0 vs. 48???16.0, p?=?0.003). Homeless women reported more symptoms on the GCS compared to non-homeless women (50???17.8 vs. 39.2???13.9, p?=?0.053). This has been revised to: On the GCS, uninsured women reported fewer symptoms overall compared to insured women (Insurance - Mean (SD): 27.2 (16.0); No Insurance - Mean (SD): 15.6 (13.1); p?=?0.003). Homeless women reported more symptoms on the GCS compared to non-homeless women (Homeless - Mean (SD): 28.7 (17.8); Not Homeless: Mean (SD): 18.0 (14.0); p?=?0.05). The article has been corrected to reflect these changes. The authors apologize for the errors.